2020
DOI: 10.3389/fnmol.2019.00302
|View full text |Cite
|
Sign up to set email alerts
|

Two Vanilloid Ligand Bindings Per Channel Are Required to Transduce Capsaicin-Activating Stimuli

Abstract: The tetrameric capsaicin receptor transient receptor potential vanilloid 1 (TRPV1) in mammals has evolved the capability to integrate pain signal arising from harmful temperature and chemical irritants. The four repetitions of TRPV1 subunits result in an ion channel with excellent pain sensitivity, allowing this ionotropic receptor to differentiate graded injuries. We manipulated the stoichiometry and relative steric coordination of capsaicin-bound structures at the molecular level to determine the rules by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…More recently, details on the stoichiometry of TRPV1 activation by capsaicin were provided by Liu and collaborators [45]. These authors used microfluorometry to measure intracellular Ca 2+ increases in HEK293 cells that expressed linked tetrameric TRPV1 receptors with different subunit compositions that contained the capsaicin-insensitive S512F mutant and/or wild-type subunits.…”
Section: Structural Overview Of the Trpv1 Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, details on the stoichiometry of TRPV1 activation by capsaicin were provided by Liu and collaborators [45]. These authors used microfluorometry to measure intracellular Ca 2+ increases in HEK293 cells that expressed linked tetrameric TRPV1 receptors with different subunit compositions that contained the capsaicin-insensitive S512F mutant and/or wild-type subunits.…”
Section: Structural Overview Of the Trpv1 Channelmentioning
confidence: 99%
“…These authors used microfluorometry to measure intracellular Ca 2+ increases in HEK293 cells that expressed linked tetrameric TRPV1 receptors with different subunit compositions that contained the capsaicin-insensitive S512F mutant and/or wild-type subunits. The authors covalently linked the subunits in order to produce all possible tetrameric compositions containing one single wild-type repeat and observed that the mutant channels could be partially opened by capsaicin and that the binding of two vanilloid molecules (i.e., two wild-type and two mutant subunits) is required in order to fully transduce capsaicin-dependent stimuli [45].…”
Section: Structural Overview Of the Trpv1 Channelmentioning
confidence: 99%
“…However, the multifunctional nature of the TRPV1 channel also poses considerable challenges for targeted drug design. Recent studies on the molecular mechanism of activation of the TRPV1 channel by capsaicin 54,55 may provide clues for new approaches to drug design.…”
Section: Future Perspectivesmentioning
confidence: 99%